FACTORS RELATED TO EXCLUSIVE BREASTFEEDING IN SUBDSTRIC OF SUKAHENING OF TASIKMALAYA IN 2010 - Neng Ayu Rosita (poltekkes kemenkes mataram, 2016)
Abstract : The aim of health development is the achievement of healthy life for every inhabitant. Based on SDKI 2006/2007 IDHS infant mortality rate 26 per 1000 live births, one of the causes is the factor of infant nutritional status, malnutrition occurs for infants fewer than 6 months. It does not need to happen if breastfeeding is given exclusively. UNICEF concludes that the coverage of exclusive breast-feeding is far from the global average which is 18%, according to SDKI 2002 the coverage of exclusive breast-feeding was 55%, in West Java 49%, in Tasikmalaya during 2009 was 70.76%, based on the data of Sukahening health centre, the coverage of exclusive breast-feeding is 64%. The research was quantitative research. The approaches were done through cross-sectional and using univariate, bivariate, and multivariate analysis. The results of the research conducted at Sukahening in 2010 showed that 77% mothers gave exclusively breast-feeding to their babies, after the bivariate test is conducted, a significant variables were mother's employment status, the counseling of breast-feeding practices, the support of parental, health personnel and husband, and the most dominant factor in the behavior of exclusive breastfeeding was parents’ supports. Therefore, the researcher suggest the need to provide the counseling of exclusive breastfeeding, and become the facilitators in the formation of KP ASI (breastfeeding Support Group), and the policy of facilitating the availability of breast-feeding corner in health facilities and public area, thus the mothers can still breastfeed exclusively, even though they are in public area.